Lebanon : Report on Performance Under the Program Supported by Emergency Post-Conflict Assistance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper focuses on Lebanon's performance under the program supported by emergency post-conflict assistance. The end-March quantitative target on international reserves was met with a wide margin. While the primary balance target was also met, the program ceiling on net government financing by the Banque du Liban (BdL) was missed. The Global Income Tax law has not yet been submitted to parliament, and the planned privatization of Telecom is waiting for an improvement in global conditions. Near-term macroeconomic policies need to focus on at least safeguarding the authorities' zero primary balance target.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet